Detección de insolvencia financiera mediante el modelo Z-Altman en empresas colombianas no cotizantes durante el periodo 2016-2019 - Roque, Daniel Isaac (2022)
Predicting the bankruptcy of a company has led to several investigations. The use of financial ratios has been proposed as an indicator to measure the stability of a business unit. Altman developed a Z-Score model, which used organization’s financial information to predict the probability of business failure 2-3 years in advance. The following work proposes the application of this model in Colombian companies to measure the probability of financial insolvency between the years 2016 and 2019. In order to fulfill the objective, the research was carried out under a quantitative approach. The results of the measurements show that the model can be applied as a predictive financial tool to measure the probability of financial insolvency of companies in Colombia. It can be concluded that Altman’s Z model can be applied to Colombian business structures to predict financial emergency situations one, two and three years in advance.